THE GIVING WILLIAM’S FLEXION EXERCISE (WFE) IS BETTER THAN BACK STRENGTHENING EXERCISE (BSE)WITH INFRA RED COMBINATION OF INTERVENTION AND MASSAGE TO DECREASE PAIN FUNCTIONAL BY THE BUILDING WORKERS WHICH SUFFER LBP MIOGENIC AT THE REGION OF DAKDAKAN ABIANTUW - Guntara, Made Aditya Yogi; Winaya, I Made Niko; Griadhi, I Putu Adhiarta; Muliarta, I Made (Majalah Ilmiah Fisioterapi Indonesia; Vol 5 No 1 (2017): Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Miogenic low back pain is lower back pain caused by disorders of the elements tendomusculer which is not accompanied by neurological disorders between the thoracic vertebra 12 and the lower pelvic and anal.  This study is an experimental research design with Pre and Post Test Control Group Design. The sampling technique is purposive sampling. The samples are 18 people of building workers at Dakdakan region with lower back pain were selected based on the scores Modified Oswestry Low Back Pain Disability Questionnaire with values> 20%. The average difference in reduction in pain scores Low Back Pain Miogenik functional groups Back Strengthening Exercise and William's Flexion Exercise groups were tested by Independent t-test.The analysis result for functional pain scores of non-specific lower back showed that the average difference in pain reduction functional non-specific lower back that is meaningful to the group Back Strengthening Exercise and the group of William's Flexion Exercise (14.55 and 22.88) with a value of p = 0.000 ( p <0.05). This indicates that the intervention of William's Flexion Exercise resulted in a decrease in pain scores of functional lower back miogenic significantly greater than the intervention of Back Strengthening Exercise Keywords:  Back Strengthening Exercise, William’s Flexion Exercise, Miogenic low back pain